Pemanfaatan Ampas Tahu Sebagai Upaya Mengelolah Menjadi Tepung Dalam Pembuat Brownies Kukus - Ratu Syafira Nurasyifa,; Melly Sukma Dewi Ratu Mutriara,; Muhammad Rizki Bima Putra ,; Sri Rezeki,; Merlin Qhardanova,; Aris Munandar, (Journal of Management and Creative Business, 2024)
This research explores the potential for using tofu dregs as an alternative raw material in making steamed brownies to reduce food industry waste. By replacing some of the wheat flour, this research assessed the impact of substitution on the color, aroma, taste, texture and appearance of steamed brownies. The experiment used a Completely Randomized Design with six levels of substitution (0%, 5%, 15%, 25%, 35%, and 45%). Organoleptic test results show that 25% substitution provides optimal quality in all aspects, confirming the potential of tofu dregs as a raw material that can improve the quality of food products while reducing industrial waste.